The effect of conjugated linoleic acid (CLA) supplementation on body anthropometric measures - Onakpoya, I; Ernst, E (Nova Science Publishers, Inc., 2012)
Overweight and obesity are public health problems of immense concern, and a variety of management strategies are currently being employed to treat the condition. The use of dietary supplements to promote weight and fat loss has become popular, and the weight loss market is awash with hundreds of such supplements. Conjugated linoleic acid (CLA) is a group of positional and geometric isomers of linoleic acid which are linked by the presence of conjugated dienes. CLA occurs naturally, and can be found in ruminant and non-ruminant animals. CLA is present in moderate amounts in dairy products, and can also be synthesized commercially for dietary consumption. CLA has been reported to possess biologic properties, including anti-carcinogenic and anti-atherogenic functions, and is also thought to improve human immune response. There is some controversy regarding the benefits of CLA on human body composition. Results from animal studies have demonstrated beneficial effects of CLA on human body composition, but findings from human clinical trials have been less than convincing. Numerous clinical trials investigating the effects of CLA on body composition have been conducted, and systematic reviews reporting the effects of CLA on weight and fat loss have been published. This chapter briefly reviews the mechanism of action of CLA, and critically analyses the available evidence from systematic reviews evaluating the efficacy and safety of CLA on various body weight parameters. © 2012 by Nova Science Publishers, Inc. All rights reserved.